Adverse events report of inactivated COVID-19 vaccine from 4040 healthcare workers. Issue 1 (2nd January 2022) - Tosun, Selma; Ozkan Ozdemir, Hülya; Erdogan, Esin; Akcay, Seniz; Aysin, Murat; Eskut, Neslihan; Ortan, Pınar; Eskut, Burak
ABSTRACT: Objectives: Numerous vaccination studies are conducted to protect against COVID-19 infection, and preclinical and clinical studies are still ongoing worldwide. During this extraordinary period, the necessity to perform COVID-19 vaccine studies and immunization programs together has emerged. Vaccine Adverse Effects (VAEs) need to be documented quickly. We aimed to determine the VAEs and to compare the frequency of VAEs between groups according to sociodemographic characteristics after the inactivated vaccine (CoronaVac) was administered to healthcare workers (HCWs) in Turkey. Methods: An online questionnaire was delivered to 4040 volunteer HCWs across the whole country who were vaccinated with CoronaVac. Sociodemographic characteristics, medical history, history of COVID-19 infection, and VAEs occurring after the first and second doses of the inactivated vaccine were evaluated. Results: The most common local and systemic VAEs after first and second doses of the COVID-19 vaccine were reported as, pain at the injection site (37.9%; 37.6%), headache (21.5%; 16.8%), fatigue (18%; 15%), drowsiness (9.6%; 8.2%), back pain (8.8%; 8.2%), nausea (6.3%; 4.8%), and joint pain (4.7%; 4.7%). Individuals with a history of allergies (generalized or vaccine-related) and females had a higher rate of VAE. Participants aged 60 and over reported less frequent VAEs. Conclusion: It is extremely important to identify and document the VAEs occurring in the early postvaccination period in different groups of the community. These initial findings may provide reassurance to healthcare providers and vaccine recipients and promote confidence in the safety of this inactive COVID-19 vaccine, however longitudinal follow-up studies are recommended.